A divergent McMurry coupling of the bis-salisaldehyde with methylene linker: The characterization of a key by-product with the possible pathway formation. Issue 5 (4th March 2017) - Darabi, Hossein Reza; Khatamifar, Ehsan; Sharifi, Ali; Aghapoor, Kioumars; Jadidi, Khosrow
ABSTRACT: The McMurry coupling of a bis-salisaldehyde3a with methyl linker as the smallest member of its alkyl series is known to give the remarkably lower yield of the corresponding stilbenophanes. The half part of this molecule, unlike bigger analogues, is a good leaving group which affords threo isomer of 4H, 4′H–4, 4′-bibenzo[d][1, 3]dioxine4 in high diastereoisomeric ratio (99>). A further study showed that the formation of this key by-product is the reason for formation of other by-products, namely, 5a, 10b-dihydrobenzofuro[2, 3-b]benzofuran9 and 2-(2, 3-dihydrobenzofuran-2-yl)phenol10 . Two reaction pathways for the formation of by-products have been proposed which are responsible for the unusual activity of dialdehyde3a . GRAPHICAL ABSTRACT: